Skill formation : policy learning from Germany? - Saniter, Andreas [Verfasser]; Eberhardt, Christiane [Verfasser] (My University, 2022)
"Collective skill formation in Germany is both highly complex and unique. Even the dual systems of other German- speaking countries show considerable differences. Focusing on four underpinning pillars (political consensus, involvement of companies, col-lective skill formation, vocational principle) of German IVET, the chapter raises the question if the German model is suitable as an example or blueprint for the development of VET in other countries. The authors address the topic from a historical perspective and refer to the experiences of the last thirty years of IVET- cooperation between Germany, the European Union and CEE countries that played a crucial role for developments. Cooperation programmes and the connected funding streams reflect the historical con-text and the role assigned to IVET in CEE countries: IVET was understood and supported as an instrument to promote the market economy (1990s), it played an essential role for EU accession (2000s) and afterwards to reduce youth unemployment via apprenticeship (2010s). The chapter concludes with an attempt to align the developments of skill forma-tion in the CEE countries with the German collective skill formation system by comparing key features of these developments with the four main pillars of the German IVET system." (Authors'abstract, BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; I 1 Internationale Berufsbildung; I 2.2 Europa; I 2.2.2 Osteuropa; 370; Berufsausbildung; Internationale Zusammenarbeit; Historische Entwicklung; Kompetenzentwicklung; Berufsbildungssystem; Bundesrepublik Deutschland; Mitteleuropa; Osteuropa